PSA-NCAM is Expressed in Immature, but not Recently Generated, Neurons in the Adult Cat Cerebral Cortex Layer II - Varea, Emilio; Belles, Maria; Vidueira, Sandra; Blasco-Ibañez, Jose Miguel; Crespo, Carlos; Pastor, Angel M.; Nacher, Juan (Frontiers in Neuroscience, 2011)
Neuronal production persists during adulthood in the dentate gyrus and the olfactory bulb, where substantial numbers of immature neurons can be found. These cells can also be found in the paleocortex layer II of adult rodents, but in this case most of them have been generated during embryogenesis. Recent reports have described the presence of similar cells, with a wider distribution, in the cerebral cortex of adult cats and primates and have suggested that they may develop into interneurons. The objective of this study is to verify this hypothesis and to explore the origin of these immature neurons in adult cats. We have analysed their distribution using immunohistochemical analysis of the polysialylated form of the neural cell adhesion molecule (PSA-NCAM) and their phenotype using markers of mature neurons and different interneuronal populations. Additionally, we have explored the origin of these cells administering 5'bromodeoxyuridine (5’BrdU) during adulthood. Immature neurons were widely dispersed in the cerebral cortex layers II and upper III, being specially abundant in the piriform and entorhinal cortices, in the ventral portions of the frontal and temporoparietal lobes, but relatively scarce in dorsal regions, such as the primary visual areas. Only a small fraction of PSA-NCAM expressing cells in layer II expressed the mature neuronal marker NeuN and virtually none of them expressed calcium binding proteins or neuropeptides. By contrast, most, if not all of these cells expressed the transcription factor Tbr-1, specifically expressed by pallium-derived principal neurons, but not CAMKII, a marker of mature excitatory neurons. Absence of PSA-NCAM/5’BrdU co-localization suggests that, as in rats, these cells were not generated during adulthood. Together, these results indicate that immature neurons in the adult cat cerebral cortex layer II are not recently generated and that they may differentiate into principal neurons.